2004
DOI: 10.1002/art.20659
|View full text |Cite
|
Sign up to set email alerts
|

Association of rheumatoid arthritis treatment response and disease duration with declines in serum levels of IgM rheumatoid factor and anti–cyclic citrullinated peptide antibody

Abstract: Objective. To examine the association of treatment response and disease duration with changes in rheumatoid factor (RF) and anti-cyclic citrullinated peptide (anti-CCP) antibody levels among patients with rheumatoid arthritis (RA).Methods. The study sample included 66 RA patients who completed double-blind, randomized clinical protocols and for whom baseline and followup serum samples were available. Anti-CCP and RF levels were measured using commercially available assay kits. Odds ratios (ORs) and 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
69
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 21 publications
15
69
1
1
Order By: Relevance
“…In our study, we have shown that, the levels of anti-CP2 were significantly increased in the serum of the C patients with RA in comparison with the controls (p < 0.001). This results in agreement with other studies [22,23].…”
Section: Discussionsupporting
confidence: 94%
“…In our study, we have shown that, the levels of anti-CP2 were significantly increased in the serum of the C patients with RA in comparison with the controls (p < 0.001). This results in agreement with other studies [22,23].…”
Section: Discussionsupporting
confidence: 94%
“…RF levels are elevated in 75% of patients with RA and this analysis is widely used for diagnosis. 25 ACPA positivity is frequently observed in patients with RA, especially in early disease, 26,27 and has a specificity approaching 100% for RA diagnosis. 28 The sensitivities of RF, ACPA and AKA in patients aged >16 years in the present study were 80.1%, 78.2% and 29.1%, respectively, and there Data presented as n (%).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CCP can be a better prognostic factor as shown in various studies. [19][20] However, we have only the RF results as a part of our previous study.…”
Section: Discussionmentioning
confidence: 99%